Entre Freud y Marcuse: algunas perspectivas metapsicológicas y críticas sociales en torno a 90la noción de represión (2018)
The road from barbarism to civilization has been possible within the framework of instinctual sublimation, in charge of relegating personal interests to repressive actions capable of counteracting the chaotic nature of the human being. In this regard, Marcuse's analysis stands out, which, without departing from Freud's theories, examines culture and ﬁnds a problem: the repression implanted went beyond human conservation to establish instrumental reasons that led to reifying and over-repressive practices. The objective of this paper is to examine this problem, integrating Freudian metapsychology with Marcuse's critical social theory. For this, a hermeneutic analytical methodology is used with which two important moments are drawn: the ﬁrst, the scheme of the philo and ontogenetic processes that have involved the drive repression; the second, highlights the repressive elements that have been superimposed in society to disrupt the spaces of sexuality, work and leisure. All in all, it is concluded that the principle of current reality, derives a performance principle that sharpens the reiﬁcation and subjects the libido to its conditions.